ANALISIS KOMPARASI REVENEW AND PROFIT SHARING PADA SISTEM MUDHARABAH PADA PT. BPRS PNM BINAMA SEMARANG (Kesesuaian dengan Fatwa DSN No. 15/DSN-MUI/IX/2000 Tentang Prinsip Bagi Hasil Usaha Dalam Lembaga Keuangan Syariah) - Hardiwinoto, - (VALUE ADDED | MAJALAH EKONOMI DAN BISNIS, 2011)
This study aims to compare the methods of profit sharing with revenew sharing in shari’ah financial principles. Shari´ah financial principles in this issue are mudaraba Shariah financial principles. The study was conducted at PT. BPRS PNM Binama. Besides comparing between profit sharing and revenew sharing also test the suitability of the fatwa of Majlis Ulama’ Indonesia No. 15/DSN-MUI/IX/2000 about Principles of operations results in Islamic Financial Institutions. PT. BPRS PNM Binama more frequent use of revenew sharing of compared with profit sharing. This is due to make it easier to calculate through revenew sharing rather than profit sharing. Kata Kunci: Mudharabah, Revenew and Profit Sharing